OPTIMALISASI PENGELOLAAN AIR LIMBAH DETERJEN DENGAN SISTEM RAWA BAMBU - T. Edy Sabli; Yusni Ikhwan Siregar; Sofia Anita; Siti Zahrah (Program Pascasarjana Universitas Riau, 2015)
ABSTRACTDomestic waste pollution has been among serious problem recently. Detergent contributed significantly lead to eutrophication as well as toxic to the environtment. A simple technology could be applicated by wetland system, in which bamboo were planted. The objective of the present study were to reduced level of detergent, Methylene Blue Active Substances (MBAS) by the bamboo wetland system. A laboratory experiment were conducted with Completely Randomized Design (CRD) with two factors including initial MBAS concentration, and residence time. Factors operating conditions were performed following Taguchi Methods. It revealed that the system has MBAS reduction efficnicy of 85,11%. The residence time significantly reduce the detergent concentration with a regression Ŷ = 12.22-0.4X2, with coeficient determination R = 79,46, apparently, four factors; initial detergent concentration, residence time, aerobic condition, and soil type (Podzolik Red Yellow) that affect the decreasing of MBAS level, with percentage of 9,11%, 8,34%, 2,68%, and 0,29% respectively.Key words: management, detergent, bamboo